Meaning-Making in Ecology Education: Analysis of Students' Multimodal Texts - Hanna Wanselin; Kristina Danielsson; Susanne Wikman (MDPI AG, 2023)
Teaching and learning in ecology depend on multimodality, involving semiotic resources such as visual representations, subject-specific symbols, and written and spoken language. Furthermore, the ecology field involves complex processes and relationships, presenting student challenges. However, more research has yet to investigate how students design multimodal texts to represent complex biological processes. For a holistic understanding of ecology, it is crucial to understand different complex processes, such as the matter cycle, energy flow, decomposition, and their relations. Therefore, this study aims to, through multimodal text analysis based on systemic functional linguistics (SFL), identify how secondary students collectively present and combine such processes and how they position themselves through their textual choices. Results indicate that representing biological processes comprises several challenges for students. One way in which this is shown is the unclear use and meaning of arrows. Thereto, the students include various aspects uncommon in the field of ecology, for example, symbols inspired by comic books, values, and the role of humans, thereby relating ecosystems to their interests and everyday life. Implications for teaching are discussed, for instance, the importance of supporting students in terms of scientific content and how to represent it, which can be conducted through text discussions.